Maternal and Neonatal Outcomes in Pregnant Women with Gestational Diabetes Mellitus Treated with Diet, Metformin or Insulin - Simeonova-Krstevska, Slagjana (Open Access Maced J Med Sci, 2018)
AIM: Aim of the study was to compare outcomes of pregnancy in gestational diabetes mellitus (GDM) treated with metformin, insulin, or diet. MATERIAL AND METHODS: The study included 48 women with GDM treated with metformin, 101 with insulin, and 200 women on a diet from the Outpatient Department of Endocrinology and University Clinic of Obstetrics and Gynecology in Skopje. RESULTS: The groups were comparable in age, smoking cigarettes and positive family history of diabetes. Mean glycosylated haemoglobin (HbA1c) at 37 gestation week, mean fasting, postprandial glycaemia, and gestational age at delivery were lower in diet and metformin than insulin group. No differences in mode of delivery were observed between the metformin and insulin group. Women in metformin group had a significantly lower incidence of LGA newborns than diet and insulin groups. The percent of SGA new-borns was higher in insulin group than diet and metformin groups. The incidence of neonatal hypoglycemia was statistically significantly higher in the insulin group than in the metformin and diet group. CONCLUSION: Metformin in women with GDM can improve maternal and neonatal outcomes compared with those treated with diet or insulin.